(untitled) (Research, Society and Development, 2022)
Engineering can be defined as the application of scientific, economic, social and practical knowledge, with the objective of creating, inventing, designing, building, maintaining and improving products and processes, through material resources and energies of nature, contributing positively to the resolution of projects of interest to society. This work aims to present an idea, born within the academic community, as a way to open space for the generation of projects that may be interesting and viable. Following a preliminary technical survey, on the production processes of sugarcane, cattle and milk, in addition to the use of energy, the idea was created to bring these processes together within an integrated format, with the insertion of complementary knowledge, from engineering areas that can foster a continuous development process, generating products, professional improvement and scientific works, in partnership with other areas of professional training. With the support of tools brought from the fundamentals of project management, a proposal for a work breakdown structure and a schedule of macro activities was arrived at. The university of Vassouras, due to having a rural experimental area in the municipality of Vassouras, has the infrastructure conditions to achieve success, once it shows interest and approves this type of initiative. It is worth remembering that before the eligibility of this idea to a potential project status, an in-depth study is necessary to validate its real viability. Therefore, submission for analysis by the university’s project incubator is an action that can become the next step.